The Limits of Atheism; Or, Why Should Sceptics Be Outlaws? - Holyoake, George Jacob, 1817-1906 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Limits of Atheism; Or, Why Should Sceptics Be Outlaws?" by George Jacob Holyoake is a philosophical treatise written in the late 19th century. This book explores the moral and civil rights of atheists and skeptics, advocating for their legal recognition and equality in society. Holyoake emphasizes a nuanced understanding of atheism, differentiating between mere negation of belief and a more affirmative stance he terms "Cosmism," which affirms the wonder and self-sufficiency of nature without necessarily denying the possibility of a higher power. In this work, Holyoake argues that atheists should not be perceived as outlaws or inferior citizens due to their beliefs. He critiques the negative connotations associated with atheism and promotes a more positive form of skepticism that values reason and reflection. By dissecting the contemporary perception of atheism, he challenges the notion that skeptical individuals must be considered morally low or socially deviant. Holyoake discusses the need for civil rights for non-believers, asserting that dismissing their perspectives contributes to a broader societal oppression. He aims to cultivate a respectful dialogue around atheism and its implications for moral philosophy and personal integrity, positioning it as a legitimate avenue for understanding the universe. (This is an automatically generated summary.)
Release date is 2011-07-20
Produced by David Widger
Keywords: Atheism